2022
DOI: 10.1038/s41598-022-22016-3
|View full text |Cite
|
Sign up to set email alerts
|

Anemia, iron deficiency, and thalassemia among the Thai population inhabiting at the Thailand-Lao PDR-Cambodia triangle

Abstract: Anemia is a major public health problem in many areas of Southeast Asia. Ascertaining anemia and defining its underlying causes is essential for providing appropriate care, management, and establishment of a control program. Limited studies on these have been carried out on people living at the borders of Thailand, Lao PDR, and Cambodia. This cross-sectional study was done in four areas along the borders of Thailand, Lao PDR, and Cambodia. Blood specimens were collected from subjects aged 15–18 years in four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Although there are various causes that give rise to anemia, iron deficiency (ID) is considered as the main cause. In certain populations, inherited Hb disorders (IHDs) have been reported to be the major determinants of anemia [4][5][6]. At the molecular level, IHDs are broadly classified into thalassemia and structural Hb variants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are various causes that give rise to anemia, iron deficiency (ID) is considered as the main cause. In certain populations, inherited Hb disorders (IHDs) have been reported to be the major determinants of anemia [4][5][6]. At the molecular level, IHDs are broadly classified into thalassemia and structural Hb variants.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of anemia can vary from population to population depending on sociodemographic characteristics and ethnic background. Regardless of ethnicity, communitybased studies in pregnant and non-pregnant women in low-and middle-income countries reported a wide range of anemia prevalence from 20-46% [4][5][6][24][25][26][27][28]. While ID was found to be the main factor explaining anemia in some studies [24][25][26][27], others reported that IHDs were the major contributing factors [4][5][6]28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications have reported the prevalence of thalassemia and hemoglobinopathies in different targeted samples and regions. To explore the prevalence of thalassemia and hemoglobinopathies in Thailand, various study designs have been conducted, such as hospital-based or regional health promotion center-based sample collection, area-based research, examining a specific group with a certain condition (a parent of the thalassemia patient, blood donors), and minority ethnic groups [ 22 , 23 , [39] , [40] , [41] , [42] , [43] , [44] ]. This study represents the prevalence report of a community-based cross-sectional study of thalassemia and hemoglobinopathies in the southern Thai population.…”
Section: Discussionmentioning
confidence: 99%
“…Community-based research has been conducted on anemia, iron deficiency, and thalassemia. Thalassemia is a major cause of anemia in the community and studied areas [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%